The Effect Of Earning Power, Leverage And Company Size On Earnings Management In Manufacturing Companies In The Cement Sub-Sector Listed On The Indonesian Stock Exchange: Pengaruh Earning Power, Leverage Dan Ukuran Perusahaan Terhadap Manajemen Laba Pada Perusahaan Manufaktur Sub Sektor Semen Yang Terdaftar Di Bursa Efek Indonesia - Annisa Fitriani; Sinta Melinda; Mega Sari (Institute of Educational, Research, and Community Service, 2023)
This study aims to determine and analyse the effect of earning power, leverage and company size on earnings management. This research was conducted at cement sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2018 period. The sampling technique used purposive sampling technique, so that 32 financial report data were obtained as research samples. The data testing method used is multiple linear regression analysis and residual test method. Based on the results of partial data testing, leverage and company size have no significant effect on earnings management actions, while earning power has a significant effect on earnings management actions